The influence of psychotherapy on obesity: Pharmacological and psychotherapeutic aspects - Literature review (Research, Society and Development, 2023)
Obesity is a worrying health condition, which affects an increasing number of people around the world, and is characterized by the excessive accumulation of body fat. Psychotherapy and pharmacotherapy can help combat this disease through different techniques. In this scenario, the objective of this research was to investigate how psychotherapy and pharmacological approaches can favor the treatment of obesity. This is a systematic review study, in which the search was carried out in the SciELO and Medline databases, using the terms: Obesity; Psychology; Psychotherapy and Pharmacology, in Portuguese and English, connected through “AND”; “OR”. The searches were carried out in September 2023. After reading 38 studies in full, only 12 aligned with the objectives of our investigation. The data presented information that emphasizes the fact that psychotherapy can positively influence the treatment of obesity, and that the pharmacological aspects associated with psychotherapeutics are viable alternatives in combating this major health problem. From this analysis, we can conclude that both psychological therapy and medications show promise in the context of obesity treatment, showing the potential to be effective. However, there is a paucity of studies addressing this issue. Therefore, it is hoped that this research can serve as a stimulus for future scientific studies that explore more broadly the relationship between psychotherapy and pharmacotherapy in the context of obesity treatment.